1991
DOI: 10.1117/12.46401
|View full text |Cite
|
Sign up to set email alerts
|

<title>Novel surface imaging masking technique for high-aspect-ratio dry etching applications</title>

Abstract: G-and i-line diazonaphthoquinone/novolak photoresist films are surface imaged with g-line, i-line and deep-UV steppers. Following optical exposure, the resist film is treated with aqueous solutions which deposit a catalyst for electroless metal deposition. Wet development of the exposed and catalyzed photoresist results in selective removal of catalyst along with the exposed portion of the underlying photoresist. Upon immersion in an aqueous electroless plating solution, metal is selectively deposited on the u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

1991
1991
1992
1992

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…Nickel is known to have superior etch resistance to Cu because the nickel halide species formed during plasma etching are much less volatile than those of copper. Etching studies have indicated that thin electroless Ni films exhibit etch selectivity of over 300:1 for photoresist (11). We have found a 400 A electroless Ni layer to be essentially unaffected during a 3.5 min RIE under conditions that yield an etch rate of 100/~/min for S i Q etch rate and 1000/~Jmin for poly-Si.…”
Section: Pattern Transfermentioning
confidence: 92%
See 3 more Smart Citations
“…Nickel is known to have superior etch resistance to Cu because the nickel halide species formed during plasma etching are much less volatile than those of copper. Etching studies have indicated that thin electroless Ni films exhibit etch selectivity of over 300:1 for photoresist (11). We have found a 400 A electroless Ni layer to be essentially unaffected during a 3.5 min RIE under conditions that yield an etch rate of 100/~/min for S i Q etch rate and 1000/~Jmin for poly-Si.…”
Section: Pattern Transfermentioning
confidence: 92%
“…For example, a crystal with a higher carbon content than another crystal may show less thermal history effects. Because carbon enhances oxygen precipitation (11). Whether or not the thermal history will show in the wafers after a heat cycle also depends on the initial interstitial oxygen content, [ It has been proposed by Shimura (13) and shown by Fraundorf et al (5) that the thermal history effect can be erased to a large extent by a high temperature treatment, 1320~ h. In this paper, it will be shown that a very short high temperature rapid thermal preannealing process (RTP), 1200~ min in argon, can reduce the thermal history effect of a subsequent two-step heat treatment by lowering the seed-end precipitation to the same level as the tang-end precipitation.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations